Comparative Perspectives on Rice Field Protection Policies in Solok City and Alor Setar - Fauziah, Hanifatul; Budhiartie, Arrie; Mohd Ridzuan, Muhammad Ameer Syazwan bin (Widya Yuridika, 2025)
Rice fields are a vital natural resource, especially in major rice-producing countries such as Indonesia and Malaysia. However, the existence of paddy fields is increasingly threatened by high land conversion due to development pressure and population growth. This research aims to compare the rice field protection policies in Solok City, Indonesia, and Alor Setar, Malaysia, and analyze their effectiveness in preventing land conversion and maintaining the sustainability of rice production. This research uses a normative method with a comparative approach, by analyzing relevant laws, regulations, and literature. The results show that the two cities have differences in the policy approach to protecting paddy fields. Solok City has comprehensive local regulations as it uses the principle of regional autonomy, while Alor Setar relies more on national laws and the role of government agencies such as MADA. However, both cities face challenges in policy implementation, especially in terms of socialization, law enforcement, and effective monitoring. This study provides policy recommendations for the improvement of sawah protection in both cities, including increased socialization, strengthened institutional capacity, increased economic incentives for farmers, and improved data and information systems. This research is expected to contribute to efforts to protect rice fields and maintain food security in Indonesia and Malaysia.